Biomechanical evaluation of femoral anteversion in developmental dysplasia of the hip and potential implications for closed reduction. (February 2020) - Huayamave, Victor; Lozinski, Blake; Rose, Christopher; Ali, Hessein; Kassab, Alain; Divo, Eduardo; Moslehy, Faissal; Price, Charles
Abstract: Background: Earlier clinical reports have identified femoral anteversion as a factor associated with developmental dysplasia of the hip. This study investigates the biomechanical influence of femoral anteversion on severe dislocations and its effect on hip reduction using the Pavlik harness. Methods: A computational model of an infant lower-extremity, representing a ten-week old female was used to analyze the biomechanics of anteversion angles ranging from 30° to 70° when severe dislocation was being treated with the Pavlik harness. Specifically, the effects and relationships between muscle passive response and femoral anteversion angle were investigated over a range of hip abduction and external rotation. Findings: Results of this study suggest that increased femoral anteversion may decrease the success rate for treatment of high-grade developmental dysplasia of the hip when using the Pavlik harness. However, hip external rotation and decreased abduction in the harness may facilitate initial reduction in these cases. Interpretation: This biomechanical study may help explain why dissections of newborn specimen with developmental dysplasia of the hip have shown normal distribution of femoral anteversion in contrast to studies of patients requiring surgery where greater frequency of increased femoral anteversion has been reported. This study also suggests that adjusting the Pavlik harness to increase external hip rotation and decrease hip abduction may facilitate initial reduction for severe dislocations with increased femoral anteversion. Highlights: Increased femoral anteversion may decrease success of Pavlik harness treatment. Hip external rotation and decreased abduction facilitates Pavlik harness treatment. Femoral anteversion influence is minimal until anteversion approaches 70°. Increased external rotation using hyperflexion could facilitate closed reduction.